PENGARUH PEMBIAYAAN MURABAHAH DAN PEMBIAYAAN IJARAH TERHADAP PROFITABILITAS PADA KOPERASI KONSUMEN SYARIAH DI KOTA BUKITTINGGI DAN KABUPATEN AGAM - Fitri Yanti; Anne Putri; Aries Tanno; Hesi Eka Puteri; Nanda Hendra (Komunitas Manajemen Kompetitif, 2026)
This study is motivated by the importance of Islamic financing management in improving the profitability of Sharia Consumer Cooperatives. Murabahah and ijarah financing are the most widely implemented contracts; however, their contributions to profitability remain inconsistent. This study aims to examine the effect of murabahah and ijarah financing on the profitability of Sharia Consumer Cooperatives in Bukittinggi City and Agam Regency. The research employed a quantitative approach with a causal associative design. Secondary data were collected from the annual financial statements of six Sharia Consumer Cooperatives during the 2020–2024 period, selected using purposive sampling. Data were analyzed using multiple linear regression with SPSS, supported by classical assumption tests, t-test, F-test, and coefficient of determination analysis. The results indicate that, partially, murabahah financing has a positive and significant effect on profitability, while ijarah financing has no significant effect. Simultaneously, murabahah and ijarah financing significantly influence profitability, with a coefficient of determination of 44.0%. It can be concluded that murabahah financing is the dominant factor contributing to cooperative profitability, whereas the optimization of ijarah financing is still needed to further improve the financial performance of Sharia Consumer Cooperatives